Profesi sebagai Pihak Pelapor atas Transaksi Keuangan yang Mencurigakan dalam Tindak Pidana Pencucian Uang - Fauziah Lubis (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2018)
The aims at this study were 1) to examine and analyze the roles and responsibilities for the profession in preventing and eradicating the crime of money laundering, 2) reviewing and analyzing professional obligations in the crime of money laundering (Money Laundering), and 3) reviewing and analyzing criminal law policies against reporting given by the profession in preventing and eradicating money laundering. This research method is a normative or doctrinal research method which is also referred to as library research or document study. The results of the study showed that 1) the role and responsibility of the profession in preventing and eradicating the crime of money laundering has not been effective, it was due to the weakness of coordination between authorized institutions, 2) criminals often use the services of professional professionals to carry out illegal transactions so that it was difficult to detect in the Banking system. for example by entering into account in the name of a lawyer, accountant, public accountant, illicit fund notary as well as the advocate profession, 3) the basic strategy of money laundering crime prevention was directed at eliminating or overcoming and improving the overall power and conditions that were criminogenic factors. the occurrence of crime is an integral approach including the asymptotic and repressive cop strategies and implementing law reform.